Influence of Friction Models on the Seismic Response of Box-Girder RC Bridges with Double Concave Friction Pendulum Bearings Under Varying Deck Aspect and Mass Ratios - Muzaffer Borekci (Buildings)
Friction pendulum bearings are widely used seismic isolation devices for bridges, with their behavior governed by friction during excitation. Sliding velocity and contact pressure are among the factors that substantially affect the friction coefficient. Common friction models include the Coulomb model, which assumes constant friction and neglects both sliding velocity and contact pressure, and the velocity-dependent model, which ignores contact pressure. This study investigates the impact of neglecting contact pressure on bridge response by additionally employing a velocity-pressure-dependent friction model and comparing the effects of these three models on the bridge response. Five 3-span box-girder RC bridges were modeled in OpenSees (v3.5.0) using Coulomb, velocity-dependent, and velocity-pressure-dependent friction models. Deck height variations were introduced to account for axial load changes on bearings. Nonlinear time history analyses were performed to evaluate seismic responses. The study also explored the effects of substructure-to-superstructure mass ratio and variations in the experimentally obtained rate parameter of velocity-dependent and velocity-pressure-dependent models. Results indicate that the velocity-pressure-dependent model provides more consistent predictions, while the rate parameter has negligible effects. The velocity-pressure-dependent model increases isolator displacement by nearly 2.5 times compared to the Coulomb and velocity-dependent models. Differences in responses are influenced more by the mass ratio than by the deck aspect ratio.